The Registration Process of Industrial Property Rights - Rosra, Deswita; ., . (International Journal of Engineering and Technology, 2018)
The objective of this article is to determine the registration process of industrial property rights. This research uses normative law method, which is a qualitative research method utilizing content analysis of secondary data. In general, the registration process of industrial property rights is by submitting the application to Directorate General of Industrial Property Rights (DJHKI) in writing in Bahasa Indonesia through filling the application form with full identities of the applicant. The application is signed by the applicant or the proxy (holder of authority) along with the attachments of the industrial property rights which are applied to the registration. The registration process of industrial property rights also has different special provisions. The research results show that the registration process of industrial property rights is regulated under Intellectual Property Rights Law and has been in conformity with International Convention.Â Â Â
Keywords: Industrial Property Rights; Proxy; Registration.